2016
DOI: 10.1128/aem.01374-16
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Konjac Flour in the Gestation Diet Changes the Gut Microbiota, Alleviates Oxidative Stress, and Improves Insulin Sensitivity in Sows

Abstract: Although dietary fibers contribute to health and physiology primarily via the fermentative actions of the gut microbiota of the hosts, few studies have focused on how these interactions influence the metabolic status of sows. Here, the effects of inclusion of konjac flour (KF) in a gestation diet on oxidative stress status, insulin sensitivity, and gut microbiota were investigated to elucidate the correlation between the microbiota and metabolic changes in sows. Sows were assigned to either control or 2.2% KF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 57 publications
5
64
2
Order By: Relevance
“…Additionally, our results showed that the potential pathogen Proteobacteria decreases from G109 to L21 in both the H and L groups. This result agrees with our previous study result showing a decreased proportion of Proteobacteria in the gut microbiota with the transition of the sows from gestation to lactation ( Tan et al, 2016 ). These changes may have a beneficial influence on metabolism, as Proteobacteria are often associated with inflammatory conditions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, our results showed that the potential pathogen Proteobacteria decreases from G109 to L21 in both the H and L groups. This result agrees with our previous study result showing a decreased proportion of Proteobacteria in the gut microbiota with the transition of the sows from gestation to lactation ( Tan et al, 2016 ). These changes may have a beneficial influence on metabolism, as Proteobacteria are often associated with inflammatory conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Several factors affect the litter performance of sows, including breed, diet, parity, backfat thickness, oxidative stress status, and milk composition. Recently, an increasing number of studies in human beings ( Koren et al, 2012 ; Hughes, 2016 ) and experiments with sows ( Tan et al, 2016 ; Zhou et al, 2017 ) suggested that the gut microbiota plays a significant role in maternal metabolism and offspring growth. Maternal microbiota can metabolize dietary components, pharmaceuticals, and toxins, which can subsequently be passed to the developing fetus or the breast-feeding neonate ( Macpherson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we found that propionate was increased in the feces and plasma of SF-fed sows. This finding is in good agreement with our previous study [23] in which we found dietary SF increased the level of cecal propionate in rats. Considering recent evidence suggesting that OCFAs can be used as a biomarker for dietary fiber intake since gut-derived propionate being used for the hepatic synthesis of OCFAs [21], we next detected the plasma NEFA concentrations of SF-fed sows.…”
Section: Discussionsupporting
confidence: 94%
“…Due to the various physicochemical properties of dietary fiber, physiological effects of dietary fiber also vary greatly as reviewed by Hamaker and Tuncil [22]. In our previous studies, we found that propionate in cecal content of rats were increased after pregelatinized waxy maize starch plus guar gum (SF) supplementation [23]. Based on these data, we hypothesize that the inclusion of SF in a gestation diet would modify the intestinal microbiota and that the modifications would be associated with changes in plasma concentrations of propionate and OCFA, insulin sensitivity and inflammatory cytokine of sows.…”
Section: Introductionmentioning
confidence: 96%
“…KGM is considered a functional fiber of food ingredient and has been consumed in the form of rubbery jelly, noodles, and other food products by humans in Asia for centuries [16]. KGM has been known to be helpful in lowering cholesterol levels, reducing weight in human beings [17], and modifying intestinal microbial metabolism in sows [18,19]. Our previous study indicated that dietary inclusion of KF with higher water-binding capacity (1.97 vs. 1.78 g/g) and swelling capacity (2.14 vs. 1.62 mL/g) than inclusion of wheat bran promoted the satiety of gestating sow [20].…”
Section: Introductionmentioning
confidence: 99%